Continuous-cropping-tolerant soybean cultivars alleviate continuous cropping obstacles by improving structure and function of rhizosphere microorganisms - Liu, Wenbo; Wang, Nan; Yao, Xingdong; He, Dexin; Sun, Hexiang; Ao, Xue; Wang, Haiying; Zhang, Huijun; St. Martin, Steven; Xie, Futi; Wang, Jingkuan (Frontiers in Microbiology, 2023)
Soybean continuous cropping will change soil microorganisms and cause continuous cropping obstacles, resulting in a significant yield decline. Different soybean cultivars have different tolerances to continuous cropping, but the relationship between continuous cropping tolerance and soil microorganisms is not clear. Two soybean cultivars with different tolerances to continuous cropping were used to study the effects of continuous cropping on soil physical and chemical properties, nitrogen and phosphorus cyclic enzyme activities, rhizosphere soil microbial community and function. The results showed that the yield reduction rate of a continuous-cropping-tolerant cultivar (L14) was lower than that of a continuous-cropping-sensitive cultivar (L10) under continuous cropping. At R1 and R6 growth stages, soil nutrient content (NH4+-N, NO3--N, AP, DOM, TK and pH), nitrogen cycling enzyme (URE, NAG, LAP) activities, phosphorus cycling enzyme (ALP, NPA, ACP) activities, copy numbers of nitrogen functional genes (AOA, AOB, nirK, nirK) and phosphorus functional genes (phoA, phoB) in L14 were higher than those in L10. Soybean cultivar was an important factor affecting the structure and functional structure of bacterial community under continuous cropping. The relative abundances of Proteobacteria, Bacteroidota, Acidobacteriota and Verrucomicrobiota with L14 were significantly higher than those of L10. The complexity of the soil bacterial community co-occurrence network in L14 was higher than that in L10. These results indicated that the continuous-cropping-tolerant soybean cultivar recruited more beneficial bacteria, changed the structure and function of microbial community, improved soil nitrogen and phosphorus cycling, and reduced the impact of continuous cropping obstacles on grain yield.